Secondary battery and electric device

By setting a conductive layer on the surface of the insulating layer to form a composite liquid collector and controlling its fineness parameters, the problems of thermal runaway and short circuit after the thickness of the secondary battery current collector is solved, and the safety and life of the battery are improved.

CN222462946UActive Publication Date: 2025-02-11SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420762166.6
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2025-02-11
Estimated Expiration
2034-04-12

AI Technical Summary

Technical Problem

The thickness of the current collector in the existing secondary batteries is easily caused by the loss of heat and short circuits.

Method used

By providing a conductive layer on at least one surface of the insulating layer, a composite liquid collector is formed, and the relationship between the conductive layer, the current collector and the roughness of the surface of the conductive layer, the current collector and the conductive layer departing from the insulating layer, the fineness parameter K of the current collector is formed, satisfying the 0.05≤K≤1.

Benefits of technology

It reduces the risk of cracks or breaks during use of the current collector, reduces the risk of thermal runaway in the secondary battery, and effectively reduces the risk of short circuits, improving the safety and life of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222462946U_ABST
    Figure CN222462946U_ABST
Patent Text Reader

Abstract

According to the secondary battery, a conductive layer is arranged on at least one surface of an insulating layer, the conductive layer and the insulating layer are combined to form a composite current collector, and the relation of the thickness D1 of the conductive layer, the thickness D2 of the current collector and the surface roughness R of the face, away from the insulating layer, of the conductive layer is limited. The density parameter K of the current collector is formed, 0.05 < = K < = 1, the composite current collector formed by combining the insulating layer and the conducting layer is adopted to replace an existing metal foil current collector, the current collector has high flexibility while the overall thickness of the current collector is reduced, and therefore the risk that the current collector cracks or fractures in the using process is reduced, and the service life of the current collector is prolonged. And the flexibility of the current collector is improved, so that the risk of burr generation during external force collision can be effectively reduced, the risk of short circuit is reduced, the use safety of the secondary battery is improved, and the service life of the secondary battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of batteries, in particular to a secondary battery and an electrical device. Background Art

[0002] Most existing secondary batteries use metal foil as the current collector, which results in the mass of the current collector accounting for a high proportion of the total weight of the existing secondary batteries, thereby affecting the energy density of the secondary batteries. However, if the thickness of the current collector is reduced, the thinner metal foil is more likely to crack or even break, which can easily lead to thermal runaway. In addition, the metal foil is prone to burrs when hit by external force, which can cause safety hazards such as short circuits. Utility Model Content

[0003] The utility model aims to provide a secondary battery and an electrical device to solve the problem that the current collector in the current secondary battery is thinned and easily causes the risk of thermal runaway and short circuit.

[0004] A first aspect of an embodiment of the present application provides a secondary battery, comprising: a current collector, the current collector being composed of an insulating layer and a conductive layer; the insulating layer having a thickness direction, along which the insulating layer has two surfaces arranged opposite to each other, and the conductive layer being arranged on at least one of the surfaces; wherein along the thickness direction, the thickness of the conductive layer is D1 μm, the thickness of the current collector is D2 μm, the surface roughness of the conductive layer on a side away from the insulating layer is R μm, the fineness parameter of the current collector is K, K=(R×D1) / D2, and satisfies: 0.05≤K≤1.

[0005] Optional, 0.21≤K≤1.

[0006] Optionally, 0.2μm≤D1≤2.5μm, or, 0.5μm≤D1≤2μm.

[0007] Optionally, 4μm≤D2≤12μm, or, 4.5μm≤D2≤10μm.

[0008] Optionally, 0<R≤5μm, or, 0.5μm≤R≤3μm.

[0009] Optionally, the tensile strength of the current collector is 150 MPa to 500 MPa, or the tensile strength of the current collector is 200 MPa to 350 MPa.

[0010] Optionally, a layer of the conductive layer is respectively disposed on the two surfaces of the insulating layer, and D1 is an average value of thicknesses of the two conductive layers in the thickness direction.

[0011] Optionally, at least one of the following characteristics is met:

[0012] a) the insulating layer comprises any one of polyethylene terephthalate, polyethylene, polypropylene, polyamide, polyimide, polyvinyl chloride, and polystyrene;

[0013] b) The conductive layer comprises any one of a metal conductive material and a carbon-based conductive material.

[0014] Optionally, the metal conductive material includes any one of aluminum, copper, nickel, titanium, silver, nickel-based alloy, aluminum-based alloy, and copper-based alloy;

[0015] The carbon-based conductive material includes any one of graphite, acetylene black, graphene, and carbon nanotubes.

[0016] A second aspect of the embodiments of the present application provides an electrical device, comprising the secondary battery as described above.

[0017] In summary, the embodiments of the present application provide a secondary battery and an electrical device having the secondary battery. The secondary battery is provided with a conductive layer on at least one surface of an insulating layer. The conductive layer and the insulating layer are combined to form a composite current collector. The relationship among the thickness D1 of the conductive layer along the thickness direction, the thickness D2 of the current collector and the roughness R of the conductive layer on the side away from the insulating layer is defined to form a fineness parameter K of the current collector, and 0.05≤K≤1. The composite current collector formed by the combination of the insulating layer and the conductive layer is used to replace the existing metal foil current collector. While reducing the overall thickness of the current collector, the current collector has higher flexibility, thereby reducing the risk of cracks or breakage of the current collector during use, reducing the risk of thermal runaway of the secondary battery, and the improvement of the flexibility of the current collector can effectively reduce the risk of burrs when impacted by external force, reduce the risk of short circuit, and improve the safety and life of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a schematic diagram of the first structure of the current collector in the secondary battery provided in the embodiment of the present application;

[0020] Figure 2 This is a schematic diagram of the second structure of the current collector in the secondary battery provided in the embodiment of the present application;

[0021] Figure 3 This is a schematic diagram of the first structure of a pole piece in a secondary battery provided in an embodiment of the present application;

[0022] Figure 4 This is a schematic diagram of the second structure of a pole piece in a secondary battery provided in an embodiment of the present application;

[0023] Figure 5 It is a schematic diagram of the structure of the secondary battery provided in the embodiment of the present application.

[0024] Description of main reference numerals:

[0025] 1. Secondary battery;

[0026] 10. current collector, 11. insulating layer, 110. surface, 111. first surface, 112. second surface, 12. conductive layer;

[0027] 20. pole piece, 21. active material layer;

[0028] 30. Shell.

[0029] X, thickness direction. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and beneficial effects of this application clearer, the following further describes this application in detail in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific implementation methods described in this specification are only for explaining this application, not for limiting this application.

[0031] In the description of the present application, it should be understood that the terms "center", "length", "width", "thickness", "up", "down", "front", "back", "horizontal", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the said features. In the description of the present application, the meaning of "multiple" refers to two or more, unless otherwise clearly and specifically defined.

[0032] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0033] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0034] This embodiment provides an electric device, including a secondary battery 1, and the secondary battery 1 serves as a power supply for the electric device. The electric device may be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship, a satellite, an energy storage system, etc.

[0035] In some embodiments of the present application, a secondary battery 1 is provided, referring to Figure 1 to Figure 4 The secondary battery 1 includes a current collector 10 , which is composed of an insulating layer 11 and a conductive layer 12 .

[0036] Reference Figure 1 to Figure 4 The insulating layer 11 has a thickness direction X. Along the thickness direction X, the insulating layer 11 has two surfaces 110 arranged opposite to each other. Figure 1 to Figure 4 In the embodiment shown, the two surfaces 110 include a first surface 111 and a second surface 112, and the conductive layer 12 is disposed on at least one surface 110 of the insulating layer 11. Figure 1 and Figure 3 In the embodiment shown, the conductive layer 12 is disposed on the first surface 111. Figure 2 and Figure 4 In the illustrated embodiment, a conductive layer 12 is disposed on the first surface 111 and the second surface 112 respectively.

[0037] Reference Figure 1 and Figure 2 , along the thickness direction X, the thickness of the conductive layer 12 is D1μm, the thickness of the current collector 10 is D2μm, the surface roughness of the conductive layer 12 on the side away from the insulating layer 11 in the thickness direction X is Rμm, and the fineness parameter of the current collector 10 is K, K=(R×D1) / D2, and satisfies: 0.05≤K≤1, specifically, the value of K can be one of 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or a range consisting of any two of them. Among them, when calculating the K value according to the equation shown in K=(R×D1) / D2, R, D1 and D2 are their respective values. It is worth noting that the above specific numerical values ​​are only given as examples, and any value within the range of 0.05≤K≤1 is within the protection scope of this application.

[0038] Specific as Figure 1 and Figure 3 In the illustrated embodiment, the conductive layer 12 is disposed on the first surface 111 , and the thickness D2 of the current collector 10 refers to the sum of the thickness D1 of the conductive layer 12 and the thickness of the insulating layer 11 in the thickness direction X.

[0039] Specific as Figure 2 and Figure 4 In the illustrated embodiment, a conductive layer 12 is disposed on the first surface 111 and the second surface 112, respectively, and the thickness of the two conductive layers 12 is the same or substantially the same, and the thickness D1 of the conductive layer 12 refers to the thickness of the conductive layer 12 on one surface of the insulating layer 11, or the thickness D1 of the conductive layer 12 refers to the average thickness of the two conductive layers 12. In the case where a conductive layer 12 is disposed on the first surface 111 and the second surface 112, respectively, and the thickness of the two conductive layers 12 differs by more than 10%, the thickness D1 of the conductive layer 12 refers to the average thickness of the two conductive layers 12. The thickness D2 of the current collector 10 refers to the sum of the thickness D1 of the conductive layer 12 and the thickness of the insulating layer 11 in the thickness direction X. The surface roughness R of the conductive layer 12 on the side away from the insulating layer 11 in the thickness direction X refers to the average surface roughness R of the two conductive layers 12.

[0040] Most existing secondary batteries use metal foil as the current collector, such as copper foil as the negative electrode current collector and aluminum foil as the positive electrode current collector. However, the mass proportion of the current collector in the secondary battery is too high, and the current collector itself does not contribute to the actual capacity of the secondary battery, thus limiting the capacity of the secondary battery. However, if the thickness of the current collector is reduced, the tensile strength and compressive deformation resistance will deteriorate, and the risk of cracks or even breakage on the foil surface will increase, which can easily lead to thermal runaway of the secondary battery. Moreover, when a secondary battery using metal foil as the current collector is subjected to external force collision, large-sized burrs are easily generated on the surface of the metal foil, which may lead to internal short circuit, thermal runaway, and even increase the risk of battery explosion and fire.

[0041] The secondary battery 1 provided in the embodiment of the present application adopts a combination of an insulating layer 11 and a conductive layer 12 to form a current collector 10. Specifically, the conductive layer 12 is arranged on at least one surface of the insulating layer 11 in the thickness direction X. The arrangement of the insulating layer 11 makes the current collector 10 have higher flexibility, which effectively reduces the risk of cracks or breaks on the surface of the current collector 10. The insulating layer 11 is used as the base layer, and the conductive layer 12 is arranged on the surface of the insulating layer 11. When the secondary battery 1 is impacted by an external force, compared with the existing current collector using metal foil as the current collector, the burrs generated on the surface of the current collector 10 are small or even no burrs are generated, and because of the barrier of the insulating layer 11, a circuit-breaking effect will occur, and even if a short circuit is caused, the short-circuit current can be prevented from increasing, thereby effectively reducing the risk of thermal runaway or even explosion and fire of the secondary battery 1, thereby improving the safety of the secondary battery 1.

[0042] In addition, in the current collector 10 of the secondary battery 1 provided in the embodiment of the present application, the thickness D1 of the conductive layer 12, the thickness D2 of the current collector 10, and the roughness R of the side of the conductive layer 12 facing away from the insulating layer 11 are correlated, and the fineness parameter K of the current collector 10 is obtained by (R×D1) / D2, and 0.05≤K≤1. When the value of the fineness parameter K is within the above range, the conductive layer 12 has a suitable thickness in the current collector 10, and the conductive performance of the current collector 10 is ensured while reducing the overall thickness D2 of the current collector 10, thereby reducing the mass proportion of the current collector 10 in the secondary battery 1 and improving the energy density of the secondary battery 1; at the same time, the current collector 10 has higher flexibility, thereby reducing the risk of cracks or breakage of the current collector 10 during use, reducing the risk of thermal runaway of the secondary battery 1, and the improvement of the flexibility of the current collector 10 can effectively reduce the risk of burrs when impacted by external force, reduce the risk of short circuit, and improve the safety and life of the secondary battery 1.

[0043] In some embodiments, 0.21≤K≤1.

[0044] In some embodiments, 0.2 μm ≤ D1 ≤ 2.5 μm, specifically, the thickness D1 of the conductive layer 12 can be 0.2 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm or any two of them. It is worth noting that the above specific values ​​are only given for example, and any value within the range of 0.2 μm ≤ D1 ≤ 2.5 μm is within the protection scope of this application. When the thickness D1 of the conductive layer 12 is within the above range, the overall thickness of the current collector 10 can be reduced while ensuring the conductive performance of the current collector 10, thereby reducing the weight of the current collector 10, reducing the mass proportion of the current collector 10 in the secondary battery 1, and improving the energy density of the secondary battery 1. It can also reduce the manufacturing cost and manufacturing difficulty of the current collector 10, and reduce the probability of burrs on the surface of the current collector 10 when the secondary battery 1 is impacted by an external force.

[0045] In some embodiments, 0.5 μm≤D1≤2 μm.

[0046] In some embodiments, 4μm≤D2≤12μm. Specifically, the thickness D2 of the current collector 10 can be one of 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm or a range consisting of any two of them. It is worth noting that the above specific values ​​are only given as examples, and any value within the range of 4μm≤D2≤12μm is within the protection scope of this application. When the thickness D2 of the current collector 10 is within the above range, the thickness of the insulating layer 11 and the conductive layer 12 in the current collector 10 are both within a suitable range. While ensuring the flexibility of the current collector 10, the overall thickness D2 of the current collector 10 is reduced, thereby reducing the weight of the current collector 10, reducing the mass proportion of the current collector 10 in the secondary battery 1, and improving the energy density of the secondary battery 1.

[0047] In some embodiments, 4.5 μm≤D2≤10 μm.

[0048] In some embodiments, reference Figure 3 and Figure 4 The secondary battery 1 includes a pole piece 20, the pole piece 20 includes a current collector 10 and an active material layer 21, and the active material layer 21 is arranged on a side of the conductive layer 12 away from the insulating layer 11 in the thickness direction X, as shown in FIG. Figure 3 In the embodiment shown, the conductive layer 12 is disposed on the first surface 111 of the insulating layer 11, and the active material layer 21 is disposed on a side of the conductive layer 12 away from the first surface 111. Figure 4In the illustrated embodiment, a conductive layer 12 is provided on the first surface 111 and the second surface 112 of the insulating layer 11, respectively, and an active material layer 21 is provided on a side of each conductive layer 12 that is away from the insulating layer 11 in the thickness direction X. Among them, when the current collector 10 is a positive electrode current collector, the active material layer 21 is a positive electrode active material layer, and the positive electrode active material layer is composed of a positive electrode active material (such as ternary material, lithium iron phosphate, etc.) of a conventional lithium ion battery, a conductive agent, an adhesive, etc., and will not be described in detail here; when the current collector 10 is a negative electrode current collector, the active material layer 21 is a negative electrode active material layer, and the negative electrode active material layer is composed of a negative electrode active material (such as graphite, silicon-based material, etc.) of a conventional lithium ion battery, a conductive agent, an adhesive, etc., and will not be described in detail here.

[0049] In some embodiments, 0<R≤5μm. Specifically, the surface roughness R of the conductive layer 12 on the side facing away from the insulating layer 11 in the thickness direction X can be 0.1μm, 0.5μm, 1.0μm, 1.5μm, 2.0μm, 2.5μm, 3.0μm, 3.5μm, 4.0μm, 4.5μm, 5.0μm or any two of them. It is worth noting that the above specific values ​​are only given for example, and any value within the range of 0<R≤5μm is within the protection scope of this application. Figure 4 In the illustrated embodiment, the surface roughness R of the conductive layer 12 on the side facing away from the insulating layer 11 in the thickness direction X refers to the average value of the surface roughness R of the two conductive layers 12. When the surface roughness R of the conductive layer 12 is within the above range, the adhesion effect between the conductive layer 12 and the active material layer 21 can be ensured, and the risk of the active material layer 21 falling off or even falling off due to the low surface roughness of the conductive layer 12 can be reduced, the current capacity of the pole piece 20 can be ensured, the safety of the secondary battery 1 can be ensured, and the energy density of the secondary battery 1 can be prevented from decreasing.

[0050] In some embodiments, 0.5 μm ≤ R ≤ 3 μm.

[0051] In some embodiments, the tensile strength of the current collector 10 is 150 MPa to 500 MPa. Specifically, the tensile strength of the current collector 10 can be one of 150 MPa, 200 MPa, 250 MPa, 300 MPa, 350 MPa, 400 MPa, 450 MPa, 500 MPa, or a range consisting of any two of them. It is worth noting that the above specific values ​​are only given by way of example, and any value of the tensile strength of the current collector 10 within the range of 150 MPa to 500 MPa is within the protection scope of the present application. When the tensile strength of the current collector 10 is within the above range, it is beneficial for the current collector 10 to have higher mechanical properties, be less likely to break or crack, and increase the life of the secondary battery 1. At the same time, it is beneficial for the current collector 10 to be less likely to break during the rolling process of manufacturing the secondary battery 1, thereby improving the yield rate, ensuring a high bonding strength between the insulating layer 11 and the conductive layer 12 and between the conductive layer 12 and the active material layer 21, effectively inhibiting the generation of microcracks on the surface of the conductive layer 12, and avoiding the conductive layer 12 and the active material layer 21 from falling off.

[0052] In some embodiments, the current collector 10 has a tensile strength of 200 MPa to 350 MPa.

[0053] In some embodiments, the insulating layer 11 includes any one of polyethylene terephthalate, polyethylene, polypropylene, polyamide, polyimide, polyvinyl chloride, and polystyrene. When one of the above polymer substances is selected as the insulating layer 11, the insulating layer 11 can have better flexibility, improve the tensile strength of the current collector 10, and reduce the risk of cracks or breakage of the current collector 10.

[0054] In some embodiments, the insulating layer 11 includes one of polyethylene terephthalate and polypropylene.

[0055] In some embodiments, the conductive layer 12 includes any one of a metallic conductive material and a carbon-based conductive material.

[0056] In some embodiments, the metal conductive material includes any one of aluminum, copper, nickel, titanium, silver, nickel-based alloys, aluminum-based alloys, and copper-based alloys.

[0057] In some embodiments, when the current collector 10 is a negative electrode current collector, the metal conductive material includes any one of copper, nickel, titanium, silver, nickel-based alloy, and copper-based alloy. In some embodiments, the metal conductive material includes one of copper and a copper-based alloy.

[0058] In some embodiments, when the current collector 10 is a positive electrode current collector, the metal conductive material includes any one of aluminum, nickel, titanium, silver, nickel-based alloy, and aluminum-based alloy. In some embodiments, the metal conductive material includes one of aluminum and an aluminum-based alloy.

[0059] In some embodiments, the carbon-based conductive material includes any one of graphite, acetylene black, graphene, and carbon nanotubes.

[0060] Reference Figure 5 The secondary battery 1 further includes a housing 30 , in which the current collector 10 is disposed.

[0061] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0062] Example 1

[0063] Preparation of negative electrode current collector:

[0064] The polypropylene after surface cleaning is placed as the insulating layer 11 in a vacuum plating chamber. At a high temperature of 1550°C, a copper-based alloy is first sputtered onto the two opposite surfaces of the polypropylene through vacuum magnetron sputtering technology with an additional cooling system in the vacuum plating chamber. The copper-based alloy is then deposited on the surface of the film layer obtained by magnetron sputtering by electroplating. Finally, a conductive layer 12 is formed by the magnetron sputtering film layer and the electroplating film layer to obtain a negative electrode current collector.

[0065] The thickness of the copper-based alloy is 1 μm, the thickness of the negative electrode current collector is 6.5 μm, and the surface roughness of the copper-based alloy facing away from the polypropylene is 0.32 μm.

[0066] Embodiments 2 to 11

[0067] The negative electrode current collector was prepared by the preparation method provided in Example 1, except for the following differences:

[0068] The type of polymer material used as the insulating layer 11 and the type of metal used as the conductive layer 12 are adjusted. The thickness of the conductive layer 12 is adjusted by adjusting the amount of metal, thereby adjusting the thickness of the negative electrode current collector. For specific data, refer to Table 1.

[0069] Comparative Example 1

[0070] Copper foil was used as the negative electrode current collector with a thickness of 6 μm.

[0071] Comparative Example 2

[0072] The negative electrode current collector was prepared by the preparation method provided in Example 1, except for the following differences:

[0073] The thickness of the conductive layer 12 is adjusted by adjusting the amount of metal, thereby adjusting the thickness of the negative electrode current collector. For specific data, refer to Table 1.

[0074] Comparative Example 3

[0075] The negative electrode current collector was prepared by the preparation method provided in Example 1, except for the following differences:

[0076] The type of polymer material used as the insulating layer 11 and the type of metal used as the conductive layer 12 are adjusted. The thickness of the conductive layer 12 is adjusted by adjusting the amount of metal, thereby adjusting the thickness of the negative electrode current collector. For specific data, refer to Table 1.

[0077] Example 12

[0078] Preparation of positive electrode current collector:

[0079] The polypropylene with surface cleaning is placed in a vacuum plating chamber as an insulating layer 11, and the aluminum-based alloy wire in the metal evaporation chamber is melted and evaporated at a high temperature of 1650°C. The evaporated aluminum-based alloy passes through a cooling system in the vacuum plating chamber and is finally deposited on the polypropylene layer to form a conductive layer 12 to obtain a positive electrode current collector.

[0080] The thickness of the aluminum-based alloy is 1 μm, the thickness of the positive electrode current collector is 10 μm, and the surface roughness of the aluminum-based alloy facing away from the polypropylene is 0.5 μm.

[0081] Examples 13 to 22

[0082] The positive electrode current collector was prepared by the preparation method provided in Example 12, except for the following differences:

[0083] The type of polymer material used as the insulating layer 11 and the type of metal used as the conductive layer 12 are adjusted. The thickness of the conductive layer 12 is adjusted by adjusting the amount of metal, thereby adjusting the thickness of the positive electrode current collector. For specific data, refer to Table 1.

[0084] Comparative Example 4

[0085] Aluminum foil was used as the positive electrode current collector with a thickness of 12 μm.

[0086] Comparative Example 5

[0087] The positive electrode current collector was prepared by the preparation method provided in Example 12, except for the following differences, the rest was the same as Example 1:

[0088] The type of polymer material used as the insulating layer 11 and the type of metal used as the conductive layer 12 are adjusted. The thickness of the conductive layer 12 is adjusted by adjusting the amount of metal, thereby adjusting the thickness of the positive electrode current collector. For specific data, refer to Table 1.

[0089] Comparative Example 6

[0090] The positive electrode current collector was prepared by the preparation method provided in Example 12, except for the following differences, the rest was the same as Example 1:

[0091] The type of polymer material used as the insulating layer 11 and the type of metal used as the conductive layer 12 are adjusted. The thickness of the conductive layer 12 is adjusted by adjusting the amount of metal, thereby adjusting the thickness of the positive electrode current collector. For specific data, refer to Table 1.

[0092] Embodiment 23

[0093] Preparation of secondary battery:

[0094] 1. Preparation of pole pieces

[0095] 1.1. Preparation of negative electrode sheet

[0096] The negative electrode active material graphite, conductive carbon black, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber latex (SBR) were fully stirred and mixed in an appropriate amount of deionized water at a weight ratio of 96.8:1.0:1.0:1.2 to form a uniform negative electrode slurry. The negative electrode slurry was coated on the negative electrode collector prepared in Example 1. After drying and other processes, the negative electrode slurry formed a negative electrode active material layer on the negative electrode collector to obtain a negative electrode sheet.

[0097] 2.2. Preparation of positive electrode sheet

[0098] The positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of N-methylpyrrolidone (NMP) solvent in a weight ratio of 96.6:1.2:2 to form a uniform positive electrode slurry. The positive electrode slurry is coated on the positive electrode collector prepared in Comparative Example 4. After drying and other processes, the positive electrode slurry forms a positive electrode active material layer on the positive electrode collector to obtain a positive electrode sheet.

[0099] 2. Preparation of electrolyte

[0100] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 3:7 are uniformly mixed to obtain an organic solvent, and then 1 mol / L LiPF6 is uniformly dissolved in the organic solvent to obtain an electrolyte.

[0101] 3. Preparation of secondary batteries

[0102] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in sequence, wherein the isolation film is made of PP (polypropylene) / PE (polyethylene) / PP composite film, and then wound into a battery cell and loaded into a shell 30, the above-mentioned electrolyte is injected into the shell 30, and it is sealed to obtain a secondary battery 1.

[0103] Embodiment 24

[0104] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0105] In step 1.1, the negative electrode current collector prepared in Example 4 is used, and in step 1.2, the positive electrode current collector prepared in Comparative Example 4 is used.

[0106] Embodiment 25

[0107] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0108] In step 1.1, the negative electrode current collector prepared in Example 6 is used, and in step 1.2, the positive electrode current collector prepared in Comparative Example 4 is used.

[0109] Embodiment 26

[0110] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0111] In step 1.1, the negative electrode current collector prepared in Example 8 is used, and in step 1.2, the positive electrode current collector prepared in Comparative Example 4 is used.

[0112] Embodiment 27

[0113] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0114] In step 1.1, the negative electrode current collector prepared in Example 9 is used, and in step 1.2, the positive electrode current collector prepared in Comparative Example 4 is used.

[0115] Embodiment 28

[0116] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0117] In step 1.1, the negative electrode current collector prepared in Example 10 is used, and in step 1.2, the positive electrode current collector prepared in Comparative Example 4 is used.

[0118] Embodiment 29

[0119] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0120] In step 1.1, the negative electrode current collector prepared in comparative example 1 is used, and in step 1.2, the positive electrode current collector prepared in example 20 is used.

[0121] Embodiment 30

[0122] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0123] In step 1.1, the negative electrode current collector prepared in comparative example 1 is used, and in step 1.2, the positive electrode current collector prepared in example 23 is used.

[0124] Embodiment 31

[0125] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0126] In step 1.1, the negative electrode current collector prepared in comparative example 1 is used, and in step 1.2, the positive electrode current collector prepared in example 24 is used.

[0127] Embodiment 32

[0128] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0129] In step 1.1, the negative electrode current collector prepared in comparative example 1 is used, and in step 1.2, the positive electrode current collector prepared in example 18 is used.

[0130] Embodiment 33

[0131] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0132] In step 1.1, the negative electrode current collector prepared in comparative example 1 is used, and in step 1.2, the positive electrode current collector prepared in example 19 is used.

[0133] Embodiment 34

[0134] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0135] In step 1.1, the negative electrode current collector prepared in comparative example 1 is used, and in step 1.2, the positive electrode current collector prepared in example 20 is used.

[0136] Embodiment 35

[0137] The secondary battery 1 was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0138] In step 1.1, the negative electrode current collector prepared in Example 6 is used, and in step 1.2, the positive electrode current collector prepared in Example 24 is used.

[0139] Comparative Example 7

[0140] A secondary battery was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0141] In step 1.1, the negative electrode current collector prepared in comparative example 1 is used, and in step 1.2, the positive electrode current collector prepared in comparative example 4 is used.

[0142] Comparative Example 8

[0143] A secondary battery was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0144] In step 1.1, the negative electrode current collector prepared in comparative example 2 is used, and in step 1.2, the positive electrode current collector prepared in comparative example 5 is used.

[0145] Comparative Example 9

[0146] A secondary battery was prepared by the preparation method provided in Example 23, except for the following differences, the rest was the same as Example 23:

[0147] In step 1.1, the negative electrode current collector prepared in comparative example 3 is used, and in step 1.2, the positive electrode current collector prepared in comparative example 6 is used.

[0148] Thickness test:

[0149] The negative electrode current collectors prepared in Examples 1 to 11 and Comparative Examples 1 to 3 were taken, and the thickness D1 of the conductive layer 12 and the total thickness D2 of the negative electrode current collector were measured using a micrometer, and the measurements were performed at 10 different positions, and the average values ​​were taken. The test results are shown in Table 1. The positive electrode current collectors prepared in Examples 12 to 22 and Comparative Examples 4 to 6 were taken, and the thickness D1 of the conductive layer 12 and the total thickness D2 of the positive electrode current collector were measured using a micrometer, and the measurements were performed at 10 different positions, and the average values ​​were taken. The test results are shown in Table 2.

[0150] Roughness test:

[0151] Take the negative electrode current collectors prepared in Examples 1 to 11 and Comparative Examples 1 to 3, and use a roughness meter to measure the roughness R of the conductive layer 12 of the negative electrode current collector away from the insulating layer 11. The measurements are performed at 10 different positions and the average value is taken. The test results are shown in Table 1.

[0152] The positive electrode current collectors prepared in Examples 12 to 22 and Comparative Examples 4 to 6 were taken, and the roughness R of the conductive layer 12 of the positive electrode current collector facing away from the insulating layer 11 was measured using a roughness meter. The measurements were performed at 10 different positions and the average value was taken. The test results are shown in Table 2.

[0153] According to the measured thickness D1 of the conductive layer 12 in the negative electrode collector, the total thickness D2 of the negative electrode collector and the roughness R of the side of the conductive layer 12 of the negative electrode collector away from the insulating layer 11, the fineness parameter K of the negative electrode collector is calculated. The calculation results are shown in Table 1.

[0154] According to the measured thickness D1 of the conductive layer 12 in the positive current collector, the total thickness D2 of the positive current collector and the roughness R of the conductive layer 12 of the positive current collector facing away from the insulating layer 11, the fineness parameter K of the positive current collector is calculated. The calculation results are shown in Table 2.

[0155] Tensile strength test of current collector 10:

[0156] The tensile strength of the negative electrode current collector was measured using an American INSTRON 3365 universal tensile testing machine. The measuring method is as follows: at room temperature (about 25° C.), the negative electrode current collectors prepared in Examples 1 to 11 and Comparative Examples 1 to 3 were cut into long strip samples (for example, samples with a width of 15 mm and a length of 150 mm), and then the samples were installed in two opposite clamps of the universal tensile testing machine. The initial length between the two clamps was set to 50 mm. The tensile test was performed at a tensile rate of 5 mm / min until the sample broke and the stretching was stopped. The maximum tensile force F that the sample was subjected to when it was broken was recorded, and the tensile strength of the negative electrode current collector was calculated according to T=F / S. The test results are shown in Table 1.

[0157] The tensile strength of the positive electrode current collector was measured using an American INSTRON 3365 universal experimental tensile testing machine. The measuring method is as follows: at room temperature (about 25°C), the positive electrode current collectors prepared in Examples 12 to 22 and Comparative Examples 4 to 6 were cut into long strip samples (for example, samples with a width of 15 mm and a length of 150 mm), and then the samples were installed in two opposite clamps of the universal experimental tensile testing machine. The initial length between the two clamps was set to 50 mm, and the tensile test was performed at a tensile rate of 5 mm / min until the sample broke and the stretching was stopped. The maximum tensile force F that the sample was subjected to when it was broken was recorded, and the tensile strength of the positive electrode current collector was calculated according to T=F / S. The test results refer to Table 2.

[0158] Pole peeling force test after rolling:

[0159] Referring to the preparation method of the negative electrode sheet provided in Example 23, the negative electrode active slurry was respectively coated on the surface of the negative electrode collector prepared in Examples 1 to 11 and Comparative Examples 1 to 3 to prepare a negative electrode sheet. The negative electrode sheet after rolling was taken, and a sample with a width of 37 mm and a length of 260 mm was taken from the center area. The steel plate (width of 50 mm and length of 400 mm) and the sample were respectively adhered to the two sides of the double-sided tape, and the steel plate was rolled back and forth along the length direction of the steel plate for 5 times with a rolling roller. A high-speed tensile test machine was used for a tensile test, and the deformation control value was set to 150 mm, the tensile speed was 50 mm / min, and the steel plate was torn along the length direction until the sample was in a free and stress-free state. The peeling force of the negative electrode sheet was measured. The test results are shown in Table 1.

[0160] Referring to the preparation method of the positive electrode sheet provided in Example 23, the positive electrode active slurry was respectively coated on the surface of the positive electrode collector prepared in Examples 12 to 22 and Comparative Examples 4 to 6 to prepare the positive electrode sheet. The rolled positive electrode sheet was taken, and a sample with a width of 37 mm and a length of 260 mm was taken from the center area. The steel plate (width of 50 mm and length of 400 mm) and the sample were respectively adhered to the two sides of the double-sided tape, and the steel plate was rolled back and forth along the length direction of the steel plate for 5 times with a rolling roller. A high-speed tensile test machine was used for a tensile test, and the deformation control value was set to 150 mm, the tensile speed was 50 mm / min, and the steel plate was torn along the length direction until the sample was in a free and stress-free state. The peeling force of the positive electrode sheet was measured, and the test results were referred to Table 2.

[0161] Pole flexibility test:

[0162] Referring to the preparation method of the negative electrode sheet provided in Example 23, the negative electrode active slurry was coated on the surface of the negative electrode current collector prepared in Examples 1 to 11 and Comparative Examples 1 to 3 to prepare the negative electrode sheet, and the negative electrode sheet after rolling was taken. Three samples with a width of 40 mm and a length of 40 mm were taken from the center area, and folded back and forth 180° three times. Under a light intensity of 1500Lx to 2500Lx, the folded gap of the negative electrode sheet was observed to see whether there was light transmission or powder falling. If light is transmitted or powder falls in the folded gap, it indicates that the flexibility of the negative electrode sheet is unqualified, otherwise, it is qualified. The test results refer to Table 1.

[0163] Referring to the preparation method of the positive electrode sheet provided in Example 23, the positive electrode active slurry was coated on the surface of the positive electrode current collector prepared in Examples 12 to 22 and Comparative Examples 4 to 6 to prepare the positive electrode sheet. The positive electrode sheet after rolling was taken, and 3 samples with a width of 40 mm and a length of 40 mm were taken from the center area, and folded back and forth 180° three times. Under a light intensity of 1500Lx to 2500Lx, the folded gap of the positive electrode sheet was observed to see whether there was light transmission or powder falling. If light is transmitted or powder falls in the folded gap, it indicates that the flexibility of the positive electrode sheet is unqualified, otherwise, it is qualified. The test results refer to Table 2.

[0164] Energy density test:

[0165] At room temperature (about 25°C), using a charge and discharge test cabinet, the secondary batteries 1 prepared in Examples 23 to 35 and the secondary batteries prepared in Comparative Examples 7 to 9 were respectively charged to 4.35V at a constant current and constant voltage of 0.33C. After standing for 15 minutes, the average voltage of the secondary batteries was read; they were discharged to 2.8V at a rate of 0.33C, and their discharge capacity was measured, which was the initial discharge capacity. After that, they were stood for 5 minutes, and then charged to 4.35V at a rate of 0.33C. The charging capacity was tested, which was the capacity of the secondary battery; the weight of the secondary battery was weighed with a Sartorius balance.

[0166] Energy density = capacity × average voltage / weight of secondary battery, unit is Wh / kg, test results refer to Table 3.

[0167] Cycle performance test:

[0168] At 45°C, the secondary batteries 1 prepared in Examples 23 to 35 and the secondary batteries prepared in Comparative Examples 7 to 9 were respectively charged to 4.2V at a constant current of 1C, then charged at a constant voltage until the current was less than or equal to 0.05C, and then discharged to 2.8V at a constant current of 1C. This is a charge and discharge cycle, and the discharge capacity of this time is the discharge capacity of the first cycle. The secondary battery was charged and discharged 1000 times according to the above method, and the discharge capacity of the 1000th cycle was recorded. The capacity retention rate of the secondary battery after 1000 cycles of 1C / 1C was calculated. The test results refer to Table 3.

[0169] Table 1

[0170]

[0171]

[0172] It can be seen from Table 1 that, referring to Examples 1 to 4 and Example 7, when the type of the conductive layer, the type of the insulating layer, the thickness of the conductive layer D1 and the thickness of the negative electrode collector D2 remain unchanged, as the surface roughness R value of the conductive layer facing away from the insulating layer increases, the fineness parameter K of the negative electrode collector increases accordingly, resulting in an increase in the peeling force of the negative electrode collector prepared in Examples 1 to 4 and Example 7 after forming a negative electrode sheet, and the tensile strength also increases accordingly. The reason is that as the surface roughness R increases, the bonding force between the conductive layer and the negative electrode active material layer in the negative electrode sheet becomes stronger, the flexibility of the negative electrode collector becomes higher, and no powder falling and light transmission occurs in the flexibility test. Referring to Examples 4 to 6, when the thickness D1 remains unchanged, as the thickness D2 and the surface roughness R increase, the fineness parameter K shows an increasing trend, which conforms to the proportional relationship between D2 and R in K = (R × D1) / D2. Referring to Examples 8 to 11, different types of insulating layers and conductive layers are used, but the thickness D1, thickness D2, surface roughness R, fineness parameter K and tensile strength of the negative electrode collector are all within the range specified in the present application, so that the negative electrode collector prepared in Examples 8 to 11 has good flexibility, and no powder loss or light transmittance occurs in the flexibility test.

[0173] In contrast, in Comparative Example 1, copper foil is used as the negative electrode current collector. Although the surface roughness R reaches 1.95, the peeling force is only 8.4N. The negative electrode sheet is prepared using the negative electrode current collector provided by Comparative Example 1. In the subsequent coating and rolling stages, the negative electrode active material layer on the negative electrode sheet and the surface of the negative electrode current collector are prone to weak adhesion, which is prone to powder loss and breakage. Powder loss and light transmittance occur during the flexibility test.

[0174] In contrast, in Comparative Example 2, the surface roughness R of the negative electrode collector is only 0.5 μm, the thickness D1 is only 0.2 μm, and the thickness D2 is only 3.5 μm, resulting in the fineness parameter of the negative electrode collector prepared in Comparative Example 2 being only 0.03, and the tensile strength of the negative electrode collector is only 120 MPa, both of which are lower than the lower limit value specified in the present application, resulting in powder loss and light transmittance in the flexibility test, indicating that the flexibility of the negative electrode collector prepared in Comparative Example 2 is poor.

[0175] In contrast, in Comparative Example 3, the surface roughness R of the negative electrode current collector is as high as 6μm, the thickness D1 is as high as 4μm, and the thickness D2 is as high as 15μm, resulting in the fineness parameter K of the negative electrode current collector being as high as 1.6, and the tensile strength of the negative electrode current collector is as high as 532MPa, both of which are higher than the upper limit value specified in the present application. Although no powder loss or light transmittance occurs in the flexibility test, the thickness of the conductive layer and the current collector are too thick, resulting in a higher weight of the negative electrode current collector, which affects the energy density of the secondary battery after being assembled into a secondary battery.

[0176] Table 2

[0177]

[0178]

[0179] It can be seen from Table 2 that, referring to Examples 12 to 15 and Example 18, when the type of the conductive layer, the type of the insulating layer, the thickness of the conductive layer D1 and the thickness of the positive electrode collector D2 remain unchanged, as the surface roughness R value of the conductive layer facing away from the insulating layer increases, the fineness parameter K of the positive electrode collector increases accordingly, resulting in an increase in the peeling force of the positive electrode collector prepared in Examples 12 to 15 and Example 18 after forming a positive electrode sheet, and the tensile strength also increases accordingly. The reason is that as the surface roughness R increases, the bonding force between the conductive layer and the positive active material layer in the positive electrode sheet becomes stronger, the flexibility of the positive electrode collector becomes higher, and no powder falling or light transmission occurs in the flexibility test. Referring to Examples 15 to 17, when the thickness D1 remains unchanged, as the thickness D2 and the surface roughness R increase, the fineness parameter K shows an increasing trend, which conforms to the proportional relationship between D2 and R in K = (R × D1) / D2. Referring to Examples 18 to 22, different types of insulating layers and conductive layers are used, but the thickness D1, thickness D2, surface roughness R, fineness parameter K and tensile strength of the positive electrode current collector are all within the range defined in this application, so that the positive electrode current collector prepared in Examples 19 to 22 has good flexibility, and no powdering and light transmission occurs in the flexibility test. Combining Tables 1 to 2, it can be seen that when the relationship in K = (R × D1) / D2 satisfies 0.05≤K≤1, the peeling force of the pole piece reaches between 8.0N and 18.0N, indicating that the active material layer in the pole piece and the current collector have a strong bonding strength; and when 0.21≤K≤1, a more excellent bonding strength is shown.

[0180] In contrast, in Comparative Example 4, aluminum foil is used as the positive electrode current collector, and its surface roughness R is only 0.31 μm, and the peeling force is only 7.2 N. The positive electrode sheet is prepared using the positive electrode current collector provided by Comparative Example 4. In the subsequent coating and rolling stages, the positive electrode active material layer on the positive electrode sheet and the positive electrode current collector surface are prone to weak adhesion, and powder loss and breakage problems may occur. Powder loss and light transmittance occur during the flexibility test.

[0181] In contrast, in Comparative Example 5, the surface roughness R of the positive electrode collector is only 0.7 μm, the thickness D1 is only 0.2 μm, and the thickness D2 is only 3.8 μm, resulting in the fineness parameter of the positive electrode collector prepared in Comparative Example 2 being only 0.04, and the tensile strength of the positive electrode collector is only 110 MPa, both of which are lower than the lower limit value specified in the present application, and the peeling force of the prepared positive electrode sheet is only 7.2 N, resulting in powder loss and light transmittance in the flexibility test, indicating that the flexibility of the positive electrode collector prepared in Comparative Example 5 is poor.

[0182] On the other hand, in Comparative Example 6, the surface roughness R of the positive electrode collector is as high as 6μm, the thickness D1 is as high as 3μm, and the thickness D2 is as high as 14μm, resulting in the fineness parameter K of the positive electrode collector being as high as 1.29, and the tensile strength of the positive electrode collector is as high as 510MPa, both of which are higher than the upper limit value specified in the present application. Although no powder loss or light transmittance occurs in the flexibility test, the thickness of the conductive layer and the current collector are too thick, resulting in a higher weight of the positive electrode collector, which affects the energy density of the secondary battery after being assembled into a secondary battery.

[0183] Table 3

[0184]

[0185]

[0186] As shown in Table 3, referring to Examples 23 to 28, the secondary batteries 1 assembled in Examples 23 to 28, the positive electrode current collector uses the aluminum foil provided in Comparative Example 4, and the negative electrode current collectors use the negative electrode current collectors prepared in Examples 1, 4, 6, 8 to 10, respectively. Under the same positive electrode current collector, with the increase of the conductive layer thickness D1, the increase of the negative electrode current collector thickness D2, and the increase of the negative electrode current collector fineness parameter K, the number of cycles, energy density, and cycle capacity retention rate of the secondary battery 1 after 1000 cycles are generally increased. Trend, referring to Example 26, the assembled secondary battery 1 uses the negative electrode collector prepared in Example 8, the thickness D1 of the conductive layer is only 0.5μm, the overall thickness D2 of the negative electrode collector is only 5.5μm, the fineness parameter K of the negative electrode collector is only 0.36, and the overall thickness of the negative electrode collector is relatively low, resulting in the energy density of the secondary battery 1 being only 270.1Wh / kg, and the cycle capacity retention rate after 1000 cycles is only 57.2%, which is lower than that of Examples 23 to 25 and Examples 27 to 28.

[0187] Referring to Examples 29 to 34, the secondary battery 1 assembled in Examples 29 to 34 uses the copper foil provided in Comparative Example 1 as the negative electrode current collector, and the positive electrode current collector uses the positive electrode current collector prepared in Examples 12 to 14 and Examples 17 to 19. With the increase of the thickness D1 of the conductive layer, the increase of the thickness D2 of the positive electrode current collector, and the increase of the fineness parameter K of the positive electrode current collector, the number of cycles, the energy density, and the cycle capacity retention rate after 1000 cycles of the secondary battery show an overall increasing trend. Referring to Example 32, the secondary battery 1 assembled therein uses the positive electrode current collector prepared in Example 19, the thickness D1 of the conductive layer is only 0.5 μm, the overall thickness D2 of the positive electrode current collector is only 9 μm, the fineness parameter K of the positive electrode current collector is only 0.21, and the overall thickness of the positive electrode current collector is relatively low, resulting in the energy density of the secondary battery 1 being only 270.1 Wh / kg, and the cycle capacity retention rate after 1000 cycles being only 57.2%, which is lower than that of Examples 29 to 31 and Examples 33 to 34.

[0188] Referring to Example 35, the secondary battery 1 assembled in Example 35 adopts the positive electrode current collector prepared in Example 15, the thickness D2 of the positive electrode current collector is 10 μm, and the fineness parameter K is 0.22. The negative electrode current collector prepared in Example 4 is adopted, the thickness D2 of the negative electrode current collector is 3.5 μm, and the fineness parameter K is 0.34. The number of cycles of the assembled secondary battery 1 is as high as 1183, the energy density is as high as 277.4 Wh / kg, and the cycle capacity retention rate after 1000 cycles is as high as 82.0%, which is better than the secondary battery 1 assembled in Examples 23 to 28 in which only the negative electrode current collector is the negative electrode current collector prepared in the examples of the present application and the positive electrode current collector is a conventional aluminum foil, and is also better than the secondary battery 1 assembled in Examples 29 to 34 in which only the positive electrode current collector is the positive electrode current collector prepared in the examples of the present application and the negative electrode current collector is a conventional copper foil.

[0189] In contrast, in Comparative Example 7, the secondary battery assembled in Comparative Example 7 uses the aluminum foil provided in Comparative Example 4 as the positive electrode current collector, and uses the copper foil provided in Comparative Example 1 as the negative electrode current collector. Since the conductivity of copper and aluminum is better than the conductivity of the conductive layer in the embodiments of the present application, the number of cycles of the secondary battery assembled in Comparative Example 7 and the cycle capacity retention rate after 1000 cycles are relatively high. However, the mass of copper and aluminum is relatively high, resulting in the energy density of the secondary battery assembled in Comparative Example 7 being lower than that of Example 35, and lower than most of the secondary batteries 1 in Examples 23 to 34.

[0190] In contrast, in Comparative Example 8, the secondary battery assembled in Comparative Example 8 uses the positive electrode current collector prepared in Comparative Example 5 and the negative electrode current collector prepared in Comparative Example 2. The thickness D1 of the conductive layer in the positive electrode current collector prepared in Comparative Example 5 and the thickness D2 of the positive electrode current collector are significantly lower, and the thickness D1 of the conductive layer in the negative electrode current collector prepared in Comparative Example 2 and the thickness D2 of the positive electrode current collector are also significantly lower, resulting in the secondary battery assembled in Comparative Example 8 having significantly poor cycle numbers and cycle capacity retention rate after 1000 cycles, and the energy density is also significantly lower than that of the secondary battery 1 assembled in Examples 23 to 35.

[0191] In contrast, in Comparative Example 9, the secondary battery assembled in Comparative Example 9 uses the positive electrode current collector prepared in Comparative Example 6 and the negative electrode current collector prepared in Comparative Example 3. The thickness D1 of the conductive layer and the thickness D2 of the positive electrode current collector in the positive electrode current collector prepared in Comparative Example 6 are significantly higher, and the thickness D1 of the conductive layer and the thickness D2 of the positive electrode current collector in the negative electrode current collector prepared in Comparative Example 3 are also significantly higher, resulting in the positive electrode current collector and the negative electrode current collector in the secondary battery in Comparative Example 9 having a mass proportion that is too high, resulting in the energy density of the assembled secondary battery being significantly lower than that of the secondary battery 1 assembled in Examples 23 to 35, and the number of cycles and the cycle capacity retention rate after 1000 cycles are also significantly poor.

[0192] The technical solutions provided by the embodiments of the present invention are introduced in detail above. The principles and implementation methods of the present invention are explained in detail using specific examples. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A secondary battery, characterized in that: include: A current collector (10), wherein the current collector (10) is composed of an insulating layer (11) and a conductive layer (12); The insulating layer (11) has a thickness direction (X), and along the thickness direction (X), the insulating layer (11) has two surfaces (110) arranged opposite to each other, and the conductive layer (12) is arranged on at least one of the surfaces; Wherein, along the thickness direction (X), the thickness of the conductive layer (12) is D1 μm, the thickness of the current collector (10) is D2 μm, the surface roughness of the conductive layer (12) facing away from the insulating layer (11) is R μm, and the fineness parameter of the current collector (10) is K, K = (R×D1) / D2, and satisfies: 0.05≤K≤1.

2. The secondary battery according to claim 1, wherein: 0.21≤K≤1。 3. The secondary battery according to claim 1, wherein: 0.2μm≤D1≤2.5μm, or, 0.5μm≤D1≤2μm.

4. The secondary battery according to claim 1, wherein: 4μm≤D2≤12μm, or, 4.5μm≤D2≤10μm.

5. The secondary battery according to claim 1, wherein: 0<R≤5μm, or, 0.5μm≤R≤3μm.

6. The secondary battery according to claim 1, wherein: The tensile strength of the current collector (10) is 150 MPa to 500 MPa, or the tensile strength of the current collector (10) is 200 MPa to 350 MPa.

7. The secondary battery according to claim 1, wherein: A layer of the conductive layer (12) is respectively arranged on the two surfaces (110) of the insulating layer (11), and D1 is an average value of the thickness of the two conductive layers (12) in the thickness direction (X).

8. The secondary battery according to claim 1, wherein: Satisfies at least one of the following characteristics: a) the insulating layer (11) comprises any one of polyethylene terephthalate, polyethylene, polypropylene, polyamide, polyimide, polyvinyl chloride and polystyrene; b) The conductive layer (12) comprises any one of a metal conductive material and a carbon-based conductive material.

9. The secondary battery according to claim 8, characterized in that The metal conductive material includes any one of aluminum, copper, nickel, titanium, silver, nickel-based alloy, aluminum-based alloy, and copper-based alloy; The carbon-based conductive material includes any one of graphite, acetylene black, graphene, and carbon nanotubes.

10. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 9.